2010
DOI: 10.1182/blood-2009-09-242347
|View full text |Cite
|
Sign up to set email alerts
|

Long-term study of indolent adult T-cell leukemia-lymphoma

Abstract: The long-term prognosis of indolent adult T-cell leukemia-lymphoma (ATL) is not clearly elucidated. From 1974 to 2003, newly diagnosed indolent ATL in 90 patients (65 chronic type and 25 smoldering type) was analyzed. The median survival time was 4.1 years; 12 patients remained alive for more than 10 years, 44 progressed to acute ATL, and 63 patients died. The estimated 5-, 10-, and 15-year survival rates were 47.2%, 25.4%, and 14.1%, respectively, with no plateau in the survival curve. Although most patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
115
3
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(128 citation statements)
references
References 26 publications
4
115
3
3
Order By: Relevance
“…However, recent report with long term follow-up of indolent ATLL (chronic and smoldering type) revealed that the median survival time was 4.1 years and the estimated 5-, 10-, 15-year survival rates were 47.2%, 25.4% and 14.1%, respectively [42]. The prognosis of indolent ATLL in this study was poorer than expected.…”
Section: Chronic Type and Smoldering Type (Indolent Type Atll)contrasting
confidence: 49%
“…However, recent report with long term follow-up of indolent ATLL (chronic and smoldering type) revealed that the median survival time was 4.1 years and the estimated 5-, 10-, 15-year survival rates were 47.2%, 25.4% and 14.1%, respectively [42]. The prognosis of indolent ATLL in this study was poorer than expected.…”
Section: Chronic Type and Smoldering Type (Indolent Type Atll)contrasting
confidence: 49%
“…8 Similarly, the so-called indolent forms (smoldering and chronic subtypes) have a poor outcome whether they are managed with watch and wait or treated with chemotherapy. 9 We recently reported the results of a worldwide meta-analysis and showed that the combination of zidovudine and IFN-alpha (IFN) is highly effective in the leukemic subtypes of ATL, and should be considered as the standard first-line therapy in that setting. 10 This combination has changed the natural history of the disease through achievement of significantly improved long-term survival in patients with smoldering and chronic ATL as well as in a subset of patients with acute ATL.…”
Section: Adult T-cell Leukemia/lymphoma (Atl) Is An Aggressive Malignmentioning
confidence: 99%
“…Interestingly, a recent investigation showed that the CCR4 expression on human CD4 + T cells is regulated by histone H3 acetylation and methylation (Singh et al, 2010). In ATLL, it was noted that the indolent type is associated with a worse survival (mean survival time: 4.1 years) (Takasaki et al, 2010), and the proliferation of HTLV-1 infected cells seems to determine the viral burden during the carrier state (Matsuoka et al, 2011). These reports suggest that early detection and treatment are essential for preventing transformation, or for decreasing the tumor burden in patients with the disease.…”
Section: Epigenetic Therapy For Leukemia/ Lymphomamentioning
confidence: 99%